Exome analysis of carotid body tumor - Anastasiya V. Snezhkina; Elena N. Lukyanova; Dmitry V. Kalinin; Anatoly V. Pokrovsky; Alexey A. Dmitriev; Nadezhda V. Koroban; Elena A. Pudova; Maria S. Fedorova; Nadezhda N. Volchenko; Oleg A. Stepanov; Ekaterina A. Zhevelyuk; Sergey L. Kharitonov; et al. (BMC, 2018)
Abstract Background Carotid body tumor (CBT) is a form of head and neck paragangliomas (HNPGLs) arising at the bifurcation of carotid arteries. Paragangliomas are commonly associated with germline and somatic mutations involving at least one of more than thirty causative genes. However, the specific functionality of a number of these genes involved in the formation of paragangliomas has not yet been fully investigated. Methods Exome library preparation was carried out using Nextera® Rapid Capture Exome Kit (Illumina, USA). Sequencing was performed on NextSeq 500 System (Illumina). Results Exome analysis of 52 CBTs revealed potential driver mutations (PDMs) in 21 genes: ARNT, BAP1, BRAF, BRCA1, BRCA2, CDKN2A, CSDE1, FGFR3, IDH1, KIF1B, KMT2D, MEN1, RET, SDHA, SDHB, SDHC, SDHD, SETD2, TP53BP1, TP53BP2, and TP53I13. In many samples, more than one PDM was identified. There are also 41% of samples in which we did not identify any PDM; in these cases, the formation of CBT was probably caused by the cumulative effect of several not highly pathogenic mutations. Estimation of average mutation load demonstrated 6-8 mutations per megabase (Mb). Genes with the highest mutation rate were identified. Conclusions Exome analysis of 52 CBTs for the first time revealed the average mutation load for these tumors and also identified potential driver mutations as well as their frequencies and co-occurrence with the other PDMs.